Dampak Kecanduan Smartphone Terhadap Kualitas Tidur Siswa SMP - Yupi Supartini; Puput Dwi Martiana; Titi Sulastri (Jurnal Keperawatan, 2021)
Excessive smartphone use has a higher risk of sleep disturbances and affects a person’s sleep quality. The purpose of this research is to determine the relationship between respondent’s characteristics and smartphone addiction to the sleep quality of adolescents at Budi Cendikia Islamic School Depok. This type of research is quantitative with a descriptive analytic approach and a cross sectional research design. The population is all 359 students. Sampling in this study using stratified random sampling technique with 112 respondents. The SAS-SV questionnaire was used to measure the level of smartphone addiction, while the PSQI questionnaire was used to measure sleep quality in adolescents. The statistical test used Chi Square and Mann Whitney with a significance level of α = 0.05. The results of the univariate statistical test showed that most of the respondents were male (52.7%), 13 years old (35.7%), had a high rate of smartphone addiction (61.6%), and poor sleep quality (70.5%). Meanwhile, the results of the bivariate statistical test showed that there was a significant difference between gender (p = 0.020) and smartphone addiction (p = 0.007) with sleep quality, but there was no significant difference between age and sleep quality (p = 0.938). This study concludes that there is a relationship between gender and smartphone addiction on students' sleep quality, but there is no relationship between age and sleep quality of students. Hence, it is necessary to limit the use of smartphones so that smartphone addiction can be minimized and sleep quality is good.”